2020
DOI: 10.3389/fmicb.2020.588009
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Identification and Functional Analysis of Circular RNAs During Rice Black-Streaked Dwarf Virus Infection in the Laodelphax striatellus (Fallén) Midgut

Abstract: Circular RNAs (circRNAs) are endogenous RNAs that have critical regulatory roles in numerous biological processes. However, it remains largely unknown whether circRNAs are induced in response to plant virus infection in the insect vector of the virus as well as whether the circRNAs regulate virus infection. Rice black-streaked dwarf virus (RBSDV) is transmitted by Laodelphax striatellus (Fallén) in a persistent propagative manner and causes severe losses in East Asian countries. To explore the expression and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…The small brown planthopper, Laodelphax striatellus (Fallén) (Hemiptera: Delphacidae), is an important short‐distance migratory pest 1 . In addition to stabbing and sucking the base of rice by adults and nymphs, they also transmit viruses such as rice black‐streaked dwarf virus 2 . At present, the control of L. striatellus mainly depends on chemical insecticides, but this has resulted in varying degrees of resistance to imidacloprid, chlorpyrifos, deltamethrin and other pesticides 3–5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The small brown planthopper, Laodelphax striatellus (Fallén) (Hemiptera: Delphacidae), is an important short‐distance migratory pest 1 . In addition to stabbing and sucking the base of rice by adults and nymphs, they also transmit viruses such as rice black‐streaked dwarf virus 2 . At present, the control of L. striatellus mainly depends on chemical insecticides, but this has resulted in varying degrees of resistance to imidacloprid, chlorpyrifos, deltamethrin and other pesticides 3–5 …”
Section: Introductionmentioning
confidence: 99%
“…1 In addition to stabbing and sucking the base of rice by adults and nymphs, they also transmit viruses such as rice black-streaked dwarf virus. 2 At present, the control of L. striatellus mainly depends on chemical insecticides, but this has resulted in varying degrees of resistance to imidacloprid, chlorpyrifos, deltamethrin and other pesticides. [3][4][5] Triflumezopyrim, a novel intermediate-ion pyrimidine insecticide from Corteva Agriscience, binds to the orthosteric site of the nicotinic acetylcholine receptor (nAChR), making the insects lethargic and poisoned, and has been gradually applied to the field control of insects having biting and sucking mouthparts such as rice planthopper and leafhopper.…”
Section: Introductionmentioning
confidence: 99%
“…For example, host circular RNA2030 inhibits RBSDV infection in SBPH via regulating its parental gene phospholipidtransporting ATPase. 15 In Aedes aegypti, long non-coding RNA-1317 is involved in the host anti-viral defense during dengue virus serotype 2 (DENV-2) infection. 29 Inhibition of lncRNA MSTRG15394 promotes RBSDV accumulation in SBPH midgut.…”
Section: Discussionmentioning
confidence: 99%
“…10 Our previous research showed that RBSDV infection resulted in a significant decrease of miR-315-5p at mRNA level. 15 However, the biological function of -miR-315-5p in plant virus-insect vector interaction is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Further experiments, such as the luciferase reporter assay for the validation of the interaction between circ_0001432 and its target miRNAs and knockdown or overexpression of circ_0001432 in vivo and in vitro, are needed to illustrate the function of circ_0001432 [ 87 ]. Furthermore, Zhang et al [ 89 ] discovered 444 novel circRNAs from the BmN cells. Of these 75 circRNAs, some have been shown to be differentially expressed during BmNPV infection.…”
Section: Circrnas In the Innate Immunity Of Insectsmentioning
confidence: 99%